Pollinating insects of cherimoya (Annona cherimola Miller) in La Molina, Lima, Peru - Morales, B. (2020)
This survey aimed to determine the pollinating insects of the flowers of the cherimoya crop (Annona cherimola Mill.) located at the Program of Research and Social Projection in Fruit Trees (PIPS-FRUTALES) at the Universidad Nacional Agraria La Molina. Fifteen trees were selected randomly, and evaluations were performed from 31 October to 15 November 2018. Three replicates were performed, each replicate was formed by a set of five trees and were evaluated in three different weeks. Each tree was evaluated in four quadrants, according to the location of the flowers (external or internal) and the floral phases of the crop (female or male). The collection of the insects from the cherimoya flowers was performed using an aspirator, then the insect morphotypes were determined and classified according to order, family, genus and/or species through the use of taxonomic dichotomous keys and the support of specialists. The collected insects belonged to the orders Coleoptera, Hymenoptera, and Hemiptera, with Coleoptera having the highest diversity (17 morphospecies) and quantity (242 specimens). The genus Europs (Monotomidae) proved to be the most abundant group of Coleoptera during the assessment period, followed by morphospecies of the families Nitidulidae, Anthicidae, Staphylinidae, Scarabaeidae, Anobiidae, and Buprestidae. The pollinating insects present in the cherimoya crop were satisfactorily classified into genera and species.